Lighting of public spaces in Malmö - Romih, Eva (2011)
This Bachelor project in landscape architecture is named Lighting of public spaces in Malmö. Purposes of this project are to examine how lighting may create enchanting rooms in the outdoor public environment, to issue guidelines for outdoor lighting and perform public space in Malmö in a more visible and creative way through proposals which make public space inviting and attractive and thus render the sense of place which is lost in the dark. First part of this project is an explanation of various aspects in lighting design and discussion about lighting now-a-days. I studied lighting designs and found inspiration in them. Through sketches, diagrams and photos I better understood the visual impact of exterior lighting. A literature study has been taken into consideration when describing different aspects and phenomenon of outdoor lighting. The second part, starting with Context, introduces the project areas in Malmö which differ from usage, position and size. Analyses of each spot are followed by a presentation of the design process showing how theory and inspirations lead to new lighting solutions within the city of Malmö. Three spots are presented together with descriptions and design proposals aiming to make the city more alive and inviting during the night. The concluding part is discussion where all parts of this project are tied together as a whole; it is an insight into results led back to the theory.